Analyzing the Correlation Between the Psychological Atmosphere and Sports Employees' Proactive Responsibility in the Sports Industry - Jingjie Zhao,; Chun Zhao,; Xinru Yu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
With the advent of the new era of employer economy, as the foundation of the enterprise operation, the enterprise staff has become an important resource for the long-term and stable development of the enterprise and the continuous acquisition of their own competitive advantages. How to mobilize the enthusiasm of employees, make employees take the initiative to take responsibility, enhance the sense of belonging to the enterprise, has become an important proposition of the current enterprise organization and management. Based on this background, from the perspective of organizational advantage, this study explores the mechanism of how organizational advantage stimulates employees' responsible behavior by creating a positive psychological atmosphere. At the same time, combined with the questionnaire data of enterprises, this study quantitatively studies the influence of psychological atmosphere on employees' responsibility behavior from the perspective of advantage. Finally, combined with the analysis results, feasible suggestions are put forward for managers to optimize their own enterprise organization and management, create a good psychological atmosphere, and stimulate employees' sense of duty performance and responsibility.